Development and optimization of a bot in Telegram for effective task management in the enterprise - V. A. Vaskin; S. D. Shibaikin; V. V. Nikulin (Вестник Дагестанского государственного технического университета: Технические науки, 2024)
Objective. The purpose of the research is to develop and implement a Telegram bot for effective task management using the functionality of the Telegram API. Method. The study is based on database design techniques. Result.The paper describes the process of developing and optimizing a Telegram bot for effective task management. As part of the research, an application was developed, implemented in Python using the Telegram API and using the PostgreSQL DBMS to store data as part of the workflow. The system is designed to optimize the workflow, manage tasks in the system and delegate them to users. A database has been designed, where the structure and relationships between data are defined, ensuring efficient storage and access to information, taking into account the needs of the application. Conclusion.The phased implementation of functionality, from task management, user notification systems, to data processing and analysis, allows us to obtain a fully functional system with a wide range of capabilities. To clarify the functions and capabilities of the bot, a demonstration of the application was carried out, reflecting the functionality of the system.